Dynamics of a small clearing flora in the biodiversity context - Balcerkiewicz, Stanisław; Pawlak, Grażyna (Biodiversity: Research and Conservation, 2006)
The present study forms a part of a multifaceted research project exploring the rate and directions of spontaneous dynamics of vegetation cover after the cessation of agricultural use, as well as the effects of anthropogenic modification of this process through controlled mowing and ploughing. Results are based on data from the experimental site located in the Wielkopolski National Park and consisting of 135 permanent 5 m x 5 m square plots. Observations in all plots were regularly repeated at 5 year intervals and, in selected plots, at additional times. The documentation covers the period from 1976 to 2003 and consists of 49675 singular floristic data entries. The objective of this work was to determine which elements of the local flora dynamics may be revealed through systematically repeated observations of permanent plots. We also aimed to understand the influence of spontaneous succession and simple agronomic treatments on the development of local biological diversity. The current paper presents the dynamics of floristic richness and diversity of a small forest clearing flora in a spatial and temporal aspect over a 25 year period. At the time of initiation of the experiment, the flora of the clearing was homogenous and dominated by segetal elements. Currently, the vegetation cover of the clearing is strongly diversified. Apart from segetal communities, there occur phytocoenoses representing fallow field, meadow, sward, forest edge and juvenile woodland stages. Over 25 years (1978-2003) this small (0.5 ha) area was inhabited by 251 species of vascular plants, including 20 species of trees and 13 species of shrubs. Ninety species have survived from 1978 and 134 species have been added since then.